Comparative In Vivo Evaluations of Curcumin and Its Analog Difluorinated Curcumin Against Cisplatin-Induced Nephrotoxicity (vol 157, pg 156, 2014) - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Muqbil, Irfana; Şahin, Nurhan; Gencoglu, Hasan; Mohammad, Ramzi M. (Humana Press Inc, 2015)
[Abstract Not Available]